Implementation of Mediation in Family Dispute Resolution Based on Islamic Law: Practices and Innovations in the Modern Era - Amaliah, Fitri (Journal of Islamic Family Law, 2025)
The resolution of family disputes based on Islamic law faces many challenges, including the rising divorce rates in Indonesia and a lack of understanding of the mediation process. Mediation as an alternative dispute resolution becomes relevant in this context. This study aims to analyze the practices of mediation in resolving family disputes and explore innovations that can enhance the effectiveness of this process in the modern era. This research employs a qualitative approach using semi-structured interviews, observations, and the distribution of questionnaires. Respondents include mediators, disputing parties, and legal practitioners, with thematic analysis techniques applied for qualitative data and descriptive statistical analysis for quantitative data. The findings indicate that mediation offers an opportunity for effective and efficient dispute resolution. However, significant challenges remain, including a lack of legal understanding, limited training for mediators, and social stigma associated with the mediation process. Innovations such as the use of online mediation applications show potential for improving accessibility and effectiveness. This study recommends enhancing education and training for mediators, as well as developing guidelines for the use of technology in mediation to increase public trust in the process.